Caracterização físico-química, sensorial e botânica de amostras de mel de Apis mellifera da Região Oeste do Paraná, Ortigueira-PR e Palmeira das Missões-RS - Arnhold, Edirlene Andréa (2016)
Honey is an ancient product with peculiarities varying with its origin, bringing innumerable benefits and easily manipulated. The present work had the objective of the physical- chemical and palynological characterization of honey samples from municipalities in the western region of Paraná, Ortigueira / PR and Palmeira das Missões / RS. This study was carried out at the State University of the West of Paraná (UNIOESTE) - Marechal Cândido Rondon - Paraná Campus, and the analyzes were carried out at the Food Analysis Laboratory of the Agrarian Sciences Center of this University from August 2014 to October 2015. A total of 167 samples of Apis. mellifera honey were collected, stored in plastic containers suitable for food, all from the 2014/2015 harvest. In the physical-chemical analyzes, when comparing samples of honey from the western region of Paraná, from the border region with those from districts far from the lake, differences were found only for determination of HMF (p <0.05). The honey color with the most prominence in the lakeside region was extra clear amber (46.74%), while towards the lake was light amber (39.53%). When comparing the separate samples of lakeside and offshore municipalities of the West region with those of the other two sites, lake border with Ortigueira and lake border with Palmeira das Missões, only differences were found in the contrast of the Lund test for lake border With Ortigueira. As for the polynic analyzes, the formation of 21 groups occurred, of which 14 have only one sample. For lake border region, the dominance of pollen types were Eugenia uniflora, Eugenia involucrata dc, Eucalyptus sp. Leucaena leucocephala, Mimosa caesalpinifolia Benth, Brachiaria sp., Oelonix regia raf., Schinus terebinthifolus, and Ipomoeae hererifolia L., and far from Lake Leucaena leucocephala, Anadenanthera colubrina, Eugenia involucrata dc, Eugenia uniflora, Citrus sp., Schinus terebinthifolus. In Palmeira das Missões, Eucalyptus sp. and Oelonix regia raf. and Ortigueira Croton floribundus, Eucalyptus sp. and Glycine max. It is concluded that in the studied regions differences were found only for HMF and Lund's Test with the predominance of extra light amber and light amber colors. The presence of Eucalyptus sp for beekeeping production since it was found in large part of the samples and Croton floribundus as characteristic plant of Ortigueira